Echocardiographic and ultrasound evaluation of haemodynamic parameters in hypoxic neonates treated with hypothermia: Study protocol - Brunets, Natalia; Brunets, Veronika; Bokiniec, Renata (Frontiers in Pediatrics, 2023)
Background Episodes of ischaemia-hypoxia in the perinatal period as well as the changes in the redistribution of blood may lead to decreased perfusion and ischaemia of the cardiac muscle. Additionally, there is a negative impact from the reduced contractility of the cardiac muscle secondary to acidosis and hypoxia. Therapeutic hypothermia (TH) improves the late effects in moderate and severe cases of hypoxia-ischaemia encephalopathy (HIE). The direct impact of TH on the cardiovascular system includes moderate bradycardia, increased pulmonary vascular resistance (PVR), inferior filling of the left ventricle (LV) and LV stroke volume. The above-mentioned consequences of TH and episodes of HI in the perinatal period are therefore exacerbation of respiratory and circulatory failure. The impact of the warming phase on the cardiovascular system is not well researched and currently few data has been published on this topic. Physiologically, warming increases heart rate, improves cardiac output and increases systemic pressure. The effect of TH and the warming phase on the cardiovascular values has a decisive impact on the metabolism of drugs, including vasopressors/inotropics, which in turn affects the choice of medication and fluid therapy. Method The study is a multi-centre, prospective, case-control, observational study. The study will include 100 neonates (50 subjects and 50 controls). Echocardiography and cerebral and abdominal ultrasound will be performed in the first 1/2 days after birth as well as during warming i.e., on day 4/7 of life. In neonatal controls these examinations will be performed for indications other than hypothermia, most frequently because of poor adaptation. Ethics and dissemination The Ethics Committee of the Medical University of Warsaw approved the study protocol prior to recruitment (KB 55/2021). Informed consent will be obtained from the carers of the neonates at the time of enrolment. Consent for participation in the study can be withdrawn at any time, without consequences and without obligation to justify the decision. All data will be stored in a secure, password-protected Excel file that is only accessible to researchers involved in the study. Findings will be published in a peer-reviewed journal and disseminated at relevant national and international conferences. Clinical Trial Registration NCT05574855.